Anti-atherosclerotic effect of incretin receptor agonists - Wang, Xin; Yang, Xin; Qi, Xiaoyan; Fan, Gang; Zhou, Lingzhi; Peng, Zhengliang; Yang, Jing (Frontiers in Endocrinology, 2024)
Incretin receptor agonists (IRAs), primarily composed of glucagon-like peptide-1 receptor agonists (GLP-1RAs) and glucose-dependent insulinotropic polypeptide receptor agonists (GIPRAs), work by mimicking the actions of the endogenous incretin hormones in the body. GLP-1RAs have been approved for use as monotherapy and in combination with GIPRAs for the management of type 2 diabetes mellitus (T2DM). In addition to their role in glucose regulation, IRAs have demonstrated various benefits such as cardiovascular protection, obesity management, and regulation of bone turnover. Some studies have suggested that IRAs not only aid in glycemic control but also exhibit anti-atherosclerotic effects. These agents have been shown to modulate lipid abnormalities, reduce blood pressure, and preserve the structural and functional integrity of the endothelium. Furthermore, IRAs have the ability to mitigate inflammation by inhibiting macrophage activation and promoting M2 polarization. Research has also indicated that IRAs can decrease macrophage foam cell formation and prevent vascular smooth muscle cell (VSMC) phenotype switching, which are pivotal in 3 atheromatous plaque formation and stability. This review offers a comprehensive overview of the protective effects of IRAs in atherosclerotic disease, with a focus on their impact on atherogenesis.